2020
DOI: 10.1177/0963689720920825
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide Enhances CAR-T Cell Activity Against Solid Tumor Cells

Abstract: Chimeric antigen receptor (CAR) T-cell immunotherapy still faces many challenges in the treatment of solid tumors, one of which is T-cell dysfunction or exhaustion. Immunomodulator lenalidomide may improve CAR T-cell function. In this study, the effects of lenalidomide on CAR T-cell functions (cytotoxicity, cytokine secretion, and cell proliferation) were investigated. Two different CAR T cells (CD133-specific CAR and HER2-specific CAR) were prepared, and the corresponding target cells including human glioma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Supporting a similar role for Ikaros in CD8 + T cells, a recent study in CAR T cell populations found that treatment of these cells with the immunomodulatory drug lenalidomide, which is known to semi‐selectively degrade Ikaros and Aiolos proteins, resulted in increased proliferation and function of these cells. This included both increased cytotoxicity and augmented expression of IL‐2, IFN‐γ, TNF‐α, and GM‐CSF, similar to the phenotype observed in T‐helper cell populations upon loss of Ikaros 88 . Finally, Ikaros may also play a role in regulating responsiveness to cytokine signals, including IL‐2, as overexpression of the dominant negative form of Ikaros resulted in increased expression of the IL‐2 receptor alpha subunit (CD25) in IL‐12 treated CD8 + cells 89 .…”
Section: Regulation Of Mature T Cell Populations By Ikaros Factorsmentioning
confidence: 66%
See 2 more Smart Citations
“…Supporting a similar role for Ikaros in CD8 + T cells, a recent study in CAR T cell populations found that treatment of these cells with the immunomodulatory drug lenalidomide, which is known to semi‐selectively degrade Ikaros and Aiolos proteins, resulted in increased proliferation and function of these cells. This included both increased cytotoxicity and augmented expression of IL‐2, IFN‐γ, TNF‐α, and GM‐CSF, similar to the phenotype observed in T‐helper cell populations upon loss of Ikaros 88 . Finally, Ikaros may also play a role in regulating responsiveness to cytokine signals, including IL‐2, as overexpression of the dominant negative form of Ikaros resulted in increased expression of the IL‐2 receptor alpha subunit (CD25) in IL‐12 treated CD8 + cells 89 .…”
Section: Regulation Of Mature T Cell Populations By Ikaros Factorsmentioning
confidence: 66%
“…However, whether this effect is due to loss of Aiolos, Ikaros, or another lenalidomide-sensitive factor is yet to be determined. 88 Regardless, the above data are supportive of a role for Aiolos, like Ikaros, in the differential regulation of pro-and anti-inflammatory cytokine production in a number of individual T-helper cell subsets.…”
Section: Ikarosmentioning
confidence: 83%
See 1 more Smart Citation
“…Besides, the loss of IKZFs is the reason for the increase of IFN-γ, IL-21, and IL-2 production by T cells treated with IMiDs ( Gandhi et al, 2014 ; Brissot et al, 2015 ). In addition, Len also decreased the levels of Ikaros and Aiolos in chimeric antigen receptor (CAR) T-cells, which helped to enhance the ability of CAR T-cells to restore IL-2 gene transcription and facilitate IL-2 secretion against solid cancer cells ( Wang et al, 2020b ).…”
Section: Targeted Therapy For Ikarosmentioning
confidence: 99%
“…In T cells, siRNA-mediated knockdown of either IKZF1 or IKZF3 is sufficient to enhance the expression of IL-2 and multiple other cytokines, reminiscent of the effects of LENA treatment 29 . We have recently demonstrated that in vitro, LENA can enhance cytokine expression and killing of solid tumors by CAR T cells, suggesting that LENA might be used for boosting the efficacy of CAR T cells targeting solid tumors 31 . However, LENA has been FDA-approved only for treating several hematological cancers (namely multiple myeloma, myelodysplastic syndromes and mantle cell lymphoma), but not for any solid tumors.…”
Section: Introductionmentioning
confidence: 99%